Pagophilus groenlandicus - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
13. Harp Seal Pagophilus groenlandicus French: Phogue du Groenland / German: Sattelrobbe / Spanish: Foca pia Other common names: Greenland Seal, Saddleback Seal Taxonomy. Phoca groenlandica Erxleben, 1777, “in Groenlandia [= Greenland] et Newfoundland.” Although D. W. Rice in 1998 recognized the subspecies oceanicus breeding in the White Sea, it 1s more common to refer to distinct populations or stocks based on morphological, genetic, and behavioral differences. Monotypic. Distribution. Subarctic in N Atlantic and Arctic oceans, from Davis Strait, Baffin I, and N Hudson Bay, to Newfoundland and Gulf of Saint Lawrence (Canada) and E to Greenland, Iceland, N Norway, White Sea, and Barents and Kara seas (N Russia). Descriptive notes. Total length ¢.160-170 cm; weight ¢.120-135 kg. Newborns are c.85 cm in length and weigh c.4 kg. Male Harp Seals can be slightly larger than females. Harp Seals are moderate-sized phocid carnivores, with robust bodies and relatively small heads. Neonates are born with a thick white lanugo (fine, soft hair) that begins to molt at about three weeks old and is replaced by short, silvery pelage with scattered small spots. Juvenile Harp Seals have similar pelages to weaned offspring and then a faint harp pattern (two longitudinal dark bands on flanks that run to just behind armpits and then upward to unite on top of shoulders) begins to appear as they age. It becomes dark black near physical maturity, particularly in males. Head of adult Harp Seals is also black. Habitat. Subarctic waters and Arctic regions of the North Atlantic Ocean, particularly tied to the southern and northern limits of seasonal pack ice. Harp Seals are closely associated with the southern extent of seasonal sea ice in late winter and spring, where they haul-out to give birth and then later to molt. They appear to be pelagic for the rest of the year because they feed and range widely in open waters and marginal sea ice. Food and Feeding. Harp Seals have a diverse diet of fish and invertebrates, but their primary prey ...